(untitled) - Neamen, Donald A (New York, 2007)
This junior level electronics text provides a foundation for analyzing and designing analog and digital electronics throughout the book. Extensive pedagogical features including numerous design examples, problem solving technique sections, Test Your Understanding questions, and chapter checkpoints lend to this classic text.
Keywords: Electronic circuit design,Semiconductors,Thiết kế mạch điện tử,Chất bán dẫn; Design and construction,Thiết kế và cấu trúc